Nutrition and physical activity recommendations for cancer survivors in Scotland: Feasibility of a short course to promote behaviour change. Issue 1 (16th February 2020) - Masson, L. F.; Douglas, F.; MacLure, K.
Abstract: More people are living for longer following a cancer diagnosis; however, long‐term survivors are more likely to experience chronic illnesses. Improving their diet and physical activity behaviours may increase survival and reduce the risk of cancer recurrence and other non‐communicable diseases. The World Cancer Research Fund and American Institute for Cancer Research recommend that cancer survivors aim to be a healthy weight and physically active; eat a diet rich in wholegrains, vegetables, fruits and beans; limit consumption of 'fast foods', red and processed meat, sugar‐sweetened drinks and alcohol; and meet nutritional needs through diet alone rather than relying on supplements. Evidence suggests that cancer survivors are receptive to receiving advice and making dietary and physical activity changes, but barriers to improving the diet and being physically active need to be explored and addressed. We collaborated with CLAN Cancer Support (an independent charity) to assess the feasibility of a 2‐day course designed to improve diet and physical activity in cancer survivors in Scotland. Further, it explored the barriers and facilitators that cancer survivors identify in relation to eating a healthy diet and being physically active. The course included presentations, practical activities and group discussions. Initial analysis indicates that factors specific to this population need to be designed into the delivery of the course to enhance recruitment and promote behaviour change. Research then needs to be translated into sustainable support programmes accessible by all cancer survivors. This article describes the rationale behind the study, its design and expected outcomes.